2012
DOI: 10.3346/jkms.2012.27.7.822
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Periodic Paralysis Associated with Transient Thyrotoxicosis Due to Painless Thyroiditis

Abstract: Thyrotoxic periodic paralysis (TPP) is a rare manifestation of hyperthyroidism characterized by muscle weakness and hypokalemia. All ethnicities can be affected, but TPP typically presents in men of Asian descent. The most common cause of TPP in thyrotoxicosis is Graves' disease. However, TPP can occur with any form of thyrotoxicosis. Up to our knowledge, very few cases ever reported the relationship between TPP and painless thyroiditis. We herein report a 25-yr-old Korean man who suffered from flaccid paralys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Only two patients with thyrotoxic periodic paralysis due to a painless thyroiditis have been reported (2,3). There are a few descriptions of fatal ventricular arrhythmias in patients with thyrotoxicosis due to Graves' disease, but only one case with painless thyroiditis has been published (2).…”
Section: Introductionmentioning
confidence: 99%
“…Only two patients with thyrotoxic periodic paralysis due to a painless thyroiditis have been reported (2,3). There are a few descriptions of fatal ventricular arrhythmias in patients with thyrotoxicosis due to Graves' disease, but only one case with painless thyroiditis has been published (2).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, based on the patient's clinical presentation and associated findings, a diagnosis of TPP due to painless thyroiditis was made. Painless thyroiditis presenting with TPP has been rarely reported [7][8][9][10][11]. A literature review revealed only 8 cases of TPP due to painless thyroiditis including our case ( Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…TPP is the most frequent form of acquired muscle paralysis in young adults [6]. The ratio of cases in males to females ranges from 17:1 to 70:1 [7].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of TPP is Graves' disease. However, TPP can occur in any type of thyrotoxicosis [6]. In general, autoimmune thyroid diseases such as Graves’ disease are more common in pubertal girls than boys.…”
Section: Discussionmentioning
confidence: 99%